Mechanical behavior and constitutive model of sustainable concrete: Seawater and sea-sand recycled aggregate concrete. (18th January 2023) - Feng, Wanhui; Tang, Yunchao; Yang, Yongmin; Cheng, Ye; Qiu, Jianhui; Zhang, Hexin; Isleem, Haytham F.; Tayeh, Bassam A.; Namdar, Abdoullah
Highlights: Seawater (SW), sea sand (SS) and recycled coarse aggregate (RA) were mixed in SWSSRAC. Effects of SW, SS, and RA on the compressive properties of SWSSRAC were studied. Stress–strain curves of SWSSRAC at three curing ages were investigated. Constitutive models for SWSSRAC at different curing ages were discussed. Abstract: Resources such as fresh water and river sand have become scarce in some areas around the world because of the considerable increase in infrastructural construction. To overcome this issue, the utilization of recycled aggregates (RAs) in concrete is considered a sustainable construction method. Due to the growing scarcity of river sand and fresh water, this study explores the mechanical properties of recycled aggregate concrete (RAC) incorporated with seawater (SW) and sea sand (SS), referred to as SWSSRAC. To this end, a total of 18 mix ratios were designed to analyze the effects of different water-to-cement ratios, curing ages, and RA replacement rates on the mechanical properties of the SWSSRAC. The results suggest that the fluidity of SWSSRAC is slightly worse than that of RAC; further, the effect of the RA replacement rate on the fluidity of concrete is greater than that of SW and SS. The stress–strain relationship reveals that the deformation capacity of SWSSRAC at curing ages of 28 and 180 days show a higher improvement attributed to SW and SS for RAC compared to that for natural aggregate concrete (NAC). In addition, using SW and SS improves the compressive strength and elastic modulus of RAC, particularly after curing for 28 days; the enhancement effect of SW and SS on the mechanical properties of RAC is higher than that of NAC. Although the unloading segments in the stress–strain relationship of SWSSRAC are different from those of RAC at the 28-day curing age, it is necessary to use constitutive models of RAC for SWSSRAC considering long-term use. According to the findings of this study, SW and SS are more suited for RAC than NAC.